Elevated serum alpha-fetoprotein in poorly differentiated adenocarcinoma with neuroendocrine differentiation of the ascending colon: a case report. Issue 1 (December 2016) - Lin, Hung-Hsin; Chang, Chia-Chu; Yang, Shung-Haur; Chang, Shih-Ching; Chen, Wei-Shone; Liang, Wen-Yih; Lin, Jen-Kou; Jiang, Jeng-Kai
Abstract Background Colorectal cancer (CRC) is the most common form of cancer and the third leading cause of death in Taiwan. Serum alpha-fetoprotein (AFP) has been extensively used as a biomarker for hepatocellular carcinoma (HCC) and yolk sac tumors. Case presentation This case report presents a 90-year-old woman with right abdominal pain and poor appetite for 1 week. The computed tomography (CT) showed wall thickening in the proximal ascending colon with ruptured appendicitis. Preoperative serum AFP was high. There was no definite liver metastasis or other abnormal findings in the hepatobiliary systems. After initial empirical antibiotic treatment, we performed laparoscopic right hemicolectomy. The pathological assessment was poorly differentiated adenocarcinoma with neuroendocrine differentiation in the ascending colon. The tumor cells did not produce AFP. Amazingly, the follow-up serum AFP level 1 month after the surgery declined to normal range. The patient had an uneventful course after the surgery and was free of recurrence or metastasis within 5 months of follow-up. Conclusions AFP may be a useful tumor marker in poorly differentiated colorectal cancer with neuroendocrine component patients and a prediction of early treatment response.